Investigations Using The Whatsapp Application By Analyzing Evidence of Crime In Conversation Data - P Priyono; Bilal Abdul Wahid; P Priatno; Risdiandri Iskandar; Ali Akbar; Arman Syah Putra (IJISTECH (International Journal of Information System and Technology), 2022)
The background of this research is to find evidence in an application called WhatsApp by analyzing data in the form of conversations or chats from 2 people who are suspected of having their conversations contain suspicious words, therefore by analyzing their conversations, errors or violations will be known conducted. The method used in this study uses the latest waterfall concept, which has been modified in order to help find answers to the problems raised. The problem raised in this study is to find evidence in the conversations carried out in the WhatsApp application. The purpose of this research is to find strong evidence so that it can be used as evidence in court and save suspicious conversation data.